Appraising the efficacy of the hybrid grid-PV power supply for a household in South Africa. (June 2021) - Mosetlhe, Thapelo; Ntombela, Mpumelelo; Yusuff, Adedayo; Ayodele, Temitope; Ogunjuyibe, Ayodeji
Highlights: A hybrid grid-photovoltaic (PV) power system for urban household. Cost of Energy is reduced from 0.14 to 0.0842. Emission of green house gases is reduced by 26%. Energy purchased from the grid is reduced as the price of energy is increased. Abstract: In this paper, the effectiveness of an hybrid grid-photovoltaic (PV) power supply for an urban household is investigated. Two parameters are used for the evaluation: (1) the cost of buying electricity and (2) the environmental benefits. Yearly energy utilisation of a household and solar irradiation are collected and used in this study. A model of a hybrid grid-PV system is developed in HOMER software to investigate the efficacy of the system in the selected site. The results show that almost 26% of operating costs could be saved yearly by implementing the hybrid supply. The emission of greenhouse gasses in service to the particular site is also reduced by 26%. The sensitivity analysis results show that the grid-PV system can be more favourable as the price of energy increases. That is, the energy purchased from the grid declines as the cost of energy purchased increases. This is also observed with the increment of both price of energy and its utilisation. A reduction of cost of energy is also observed.